Blast exposure results in tau and neurofilament light chain changes in peripheral blood. (28th July 2020) - Edwards, Katie A.; Leete, Jacqueline J.; Tschiffely, Anna E.; Moore, Candace Y.; Dell, Kristine C.; Statz, Jonathan K.; Carr, Walter; Walker, Peter B.; LoPresti, Matthew L.; Ahlers, Stephen T.; Yarnell, Angela M.; Gill, Jessica
ABSTRACT: Objectives: To evaluate how blast exposure impacts peripheral biomarkers in military personnel enrolled in 10-day blast training. Methods: On day 7, 21 military personnel experienced peak overpressure <2 pounds per square inch (psi); while 29 military personnel experienced peak overpressure ≥5 psi. Blood samples were collected each day to measure changes in amyloid beta (Aβ), neurofilament light chain (NFL), and tau concentrations. Results: Within 24 hours following exposure ≥5 psi, the ≥5 psi group had lower Aβ42 ( p = .004) and NFL ( p < .001) compared to the <2 psi group and lower Aβ42 (9.35%) and NFL (22.01%) compared to baseline. Twenty-four hours after ≥5 psi exposure, the ≥5 psi group had lower tau ( p < .001) and NFL ( p < .001) compared to the <2 psi group and baseline. Seventy-two hours after exposure ≥5 psi, tau increased in the ≥5 psi group compared to the <2 psi group ( p = .02) and baseline. The tau:Aβ42 ratio 24 hours after blast ( p = .012), and the Aβ40:Aβ42 ratio 48 hours after blast ( p = .04) differed in the ≥5 psi group compared to the <2 psi group. Conclusions: These findings provide an initial report of acute alterations in biomarker concentrations following blast exposure.